Authority of the superior commander in commanding and leading subordinates - Ryszard Kałużny (Scientific Journal of the Military University of Land Forces, 2024)
The author addresses the problem of the superior’s authority and its importance in commanding subordinates in uniformed services. Based on the analysis of the source literature and his own experiences, he defines the concept of authority and interprets its types. In the context of reflections on the subject of authority, he also defines the concepts of command and leadership and indicates the positive consequences of liberating authority but also to the negative implications of authoritarian management of subordinates.